Revisiting Solvency And Liquidity Analysis In Commercial Banks: A Literature Review With Insights From Emerging Markets - Laith Ahmad Mohammad Alkasasbeh; Dr. Padma C (Journal of Informatics Education and Research, 2025)
Solvency and liquidity are critical dimensions of financial stability and operational efficiency in commercial banking, particularly within the volatile and resource-constrained environments of emerging markets. This review synthesizes theoretical foundations and empirical research on the relationship between solvency and liquidity, focusing on their relevance to risk management, capital planning, and regulatory oversight. Drawing upon studies from diverse emerging economies including Jordan, Indonesia, Nigeria, and Pakistan this article explores the application of traditional metrics such as the debt-equity ratio (DER), capital adequacy ratio (CAR), current ratio (CR), and liquidity coverage ratio (LCR). The findings indicate a persistent reliance on static ratio analysis and limited integration of dynamic tools such as stress testing, real-time solvency dashboards, or macro-financial scenario modeling. The review highlights emerging trends in digital financial reporting, ESG-linked solvency concerns, and regulatory reforms under Basel III. Despite advances, significant gaps remain in the literature, particularly regarding integrated solvency–liquidity frameworks, cross-country comparisons, and the role of technology and sustainability. This paper concludes by outlining policy and practice implications for bank regulators, financial managers, and analysts, and calls for future research that bridges solvency and liquidity through dynamic, data-driven, and sustainability-oriented approaches. Addressing these gaps is vital for enhancing financial resilience, regulatory compliance, and sustainable banking development in emerging markets.